An NMR-compatible microfluidic platform enabling in situ electrochemistry. Issue 17 (31st July 2020) - Davoodi, Hossein; Nordin, Nurdiana; Bordonali, Lorenzo; Korvink, Jan G.; MacKinnon, Neil; Badilita, Vlad
Abstract : Integrating precisely-oriented micro-electrodes and NMR micro-coils enables in situ monitoring of electrochemistry processes. Abstract : Combining microfluidic devices with nuclear magnetic resonance (NMR) has the potential of unlocking their vast sample handling and processing operation space for use with the powerful analytics provided by NMR. One particularly challenging class of integrated functional elements from the perspective of NMR are conductive structures. Metallic electrodes could be used for electrochemical sample interaction for example, yet they can cause severe NMR spectral and SNR degradation. These issues are more entangled at the micro-scale since the distorted volume occupies a higher ratio of the sample volume. In this study, a combination of simulation and experimental validation was used to identify an electrode geometry that, in terms of NMR spectral parameters, performs as well as for the case when no electrodes are present. By placing the metal tracks in the side-walls of a microfluidic channel, we found that NMR RF excitation performance was actually enhanced, without compromising B 0 homogeneity. Monitoring in situ deposition of chitosan in the microfluidic platform is presented as a proof-of-concept demonstration of NMR characterisation of an electrochemical process.